Co-Ti-O complex oxides: Hydrothermal synthesis, phase characterization, color analysis and catalytic activity assessment - Apinpus Rujiwatra (2018)
© 2015, Chiang Mai University. All rights reserved. The hydrothermal synthesis of Co-Ti-O complex oxide nanoparticles from the reaction between TiO2and Co(NO3)2.6H2O using the stoichiometric ratio to yield Co2TiO4and NaOH as mineralizer have been investigated. The particles were characterized by powder X-ray diffraction, selected area electron diffraction, scanning electron and transmission electron microscopies, UV-Vis, infrared and Raman spectroscopies, X-ray absorption near-edge spectroscopy, thermogravimetric analysis and gas sorption measurements. Evidences on the pathogenic formation of Co3O4and CoTiO3are illustrated, and the unlikely in yielding a single phase of Co2TiO4is revealed. Detailed phase characterization is discussed. The particles showed a dark bluish green color, two different morphologies of rhombus and needle shape with a mean particle size of 150 nm, a remarkably narrow pore size distribution below 75 Å, and type II gas sorption behavior. An excellent performance as a catalyst toward the Fischer-Tropsch synthesis with 35% of CO conversion and a high selectivity toward the C10, has been revealed.